A Defected Ground Structure without Ground Contact Problem and Application to Branch Line Couplers - Jongsik Lim; Dal Ahn; Sang-Min Han; Yongchae Jeong; Haiwen Liu (International Journal of Antennas and Propagation)
A new defected ground structure (DGS) microstrip line that is free from the ground contact problem is described together with its application example. The proposed DGS microstrip line adopts a double-layered substrate. The first layer contains the microstrip line and DGS patterns on the top and bottom planes as with the conventional DGS line. The second substrate, of which upper metal plane has already been removed, is attached to the bottom ground plane of the first layer. This structure prevents the ground plane of the first substrate with DGS patterns from making contact with the metal housing. The proposed DGS microstrip line has advantageous transmission and rejection characteristics, without the ground contact problem of DGS patterns, which has been a critical problem of previous DGS lines. A 10 dB branch line hybrid coupler is designed and measured, as an example of application of the proposed DGS microstrip line.